PENGARUH DISIPLIN BELAJAR DAN PEMBERIAN PEKERJAAN RUMAH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD GUGUS RA KARTINI KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Prianca Trisna Ekawati; Lisa Virdinarti Putra (Badan Penerbit STIEPARI Press, 2022)
Problems in grade III students of SD Cluster RA Kartini, East Ungaran Sub-district, Semarang Regency showed that the final test scores for the first semester of mathematics subjects had different completeness for each school. Based on interviews with teachers, the factors that influence the learning outcomes of mathematics are student learning discipline. There are some students who cannot manage their study time. In addition, because of the giving of homework, there were some students who were not orderly in doing their homework. The research method uses ex post facto quantitative research methods. The sampling technique used proportionate stratified random sampling, and obtained a sample of 98 students. The results of the study show: (1) the results of a simple linear regression test show the R square value of 0.123, a significance value of 0.000, meaning that learning discipline has a significant effect on learning outcomes in Mathematics positively by 12.3%. (2) the results of a simple linear regression test show that the R square value is 0.109, a significance value of 0.001 means that giving homework has a significant effect on learning mathematics outcomes positively by 10.9%. (3) the results of the simple linear regression test show that the R square value is 0.181, the significance value is 0.000, meaning that learning discipline and giving homework have a significant effect on positive mathematics learning outcomes by 18.1%.